The psychology of color in business branding: how color influences purchasing decisions - Nuresa, Difa (Asian Journal of Multidisciplinary Research, 2025)
Color is a visual element that has a significant psychological impact on consumer purchase decisions. Color psychology in business branding plays a role in building brand identity, creating emotional associations, and increasing product appeal in the market. Various studies show that color has an influence on consumer perceptions, emotions, and behavior, so the choice of color in marketing strategies can determine the success of a brand. However, while many companies have adopted color-based strategies, there is still a gap in understanding how certain color combinations can affect customer loyalty and market preferences in the long run. This study aims to analyze the role of color psychology in business branding and its impact on consumer purchasing decisions. The method used in this study is a literature study with a qualitative approach, in which various academic sources, such as scientific journals and research reports in the last five years, are systematically reviewed to identify patterns and trends relevant to this topic. The results of the study show that color in branding not only affects visual appeal but also forms a deep emotional impression on consumers. The color red, for example, is often associated with energy and urgency, while the color blue reflects professionalism and trust. In addition, cultural and demographic factors also affect consumer perception of certain colors. Therefore, companies need to understand color psychology in more depth to design effective branding strategies and increase competitiveness in the market.